Green Management Practices and Organisational Efficiency in a Higher Institution - Oladele Thomas Oyetunde; Oyenuga Michael Oyedele; Adoga Gloria Jaccinta (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2023)
The seventeen United Nations Sustainable Development Goals have become an umbrella which houses many organisational functions and indeed the issue of sustainability has become a major force to be reckoned with in today’s world. One of the ways to become sustainable is by going ‘green’, hence this study set out to evaluate the effects of green management practices on the organizational efficiency in a higher institution. With three other sub-objectives, the study  evaluated the effect of green management policy on organisational efficiency, examined the effect of green technology on organisational efficiency and evaluated the effect of green waste management on the organisational efficiency of Veritas University using the Sustainability Theory as its anchor. One hundred and ninety-nine members of staff out of the three hundred and ninety-six formed the sample of the study and they were able to respond to questions using  questionnaire as the research instrument. The data analysis technique used for this study was regression and correlation analysis using SPSS with hypotheses tested at 5% level of o=significance. From the findings of the study, it was discovered that the institution employed green policy, green technology, and green waste management and cumulative influence of all green management policy and green technology significant at 5% while green waste management is significant at 10%. Finally, the study concluded that management of higher institutions should increase their engagement in environmentally friendly policies in order to have a more positive impact on the community, which will boost productivity and employee performance.